PERAN PEMERINTAH RUPAT UTARA DALAM PENANGGULANGAN ILLEGAL FISHING DI PERBATASAN SELAT MALAKA - Qalbi Fitrah; Tuah Kalti Takwa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The Malacca Strait border region is a narrow area separating North Rupat, Indonesia, from Malacca, Malaysia. The Strait of Malacca varies considerably in width, ranging from 27 to 115 Nautical Miles (NM). The Strait, separating North Rupat from Malacca, Malaysia, is only about 20.99 Nautical Miles (NM). It is a highly strategic fishing and shipping zone, but is highly vulnerable to illegal practices, both from North Rupat and from abroad, including neighboring Malaysia. This study employed qualitative methods, collecting survey data from fishermen and the local government of North Rupat District. The theory used is regime compliance, to determine whether the regulations implemented in North Rupat are in accordance with the provisions of UNCLOS 1982. The constructivist perspective used is commonly used in conjunction with regime theory. This perspective explains that regional regulations are adopted from the international regime. The results of this study that the North Rupat government has implemented a series of efforts, including outreach and patrols, to address the practice of fishermen taking fish into Malaysian waters. These efforts have succeeded in reducing the number of small-scale fishermen taking and selling fish in the area by 2024. Keywords: Government Role, Illegal Fishing, Border, Malacca Strait, North Rupat.